A multicenter review of undescended testis torsion: A plea for early management. Issue 2 (April 2021) - Dupond-Athénor, Adrien; Peycelon, Matthieu; Abbo, Olivier; Rod, Julien; Haraux, Elodie; Scalabre, Aurélien; Arnaud, Alexis; Guérin, Florent; Irtan, Sabine
Summary: Introduction: Torsion of an undescended testis (UT) is a surgical emergency, difficult to diagnose, whose prognosis depends on a quick management. Aim of the study: To evaluate the management and outcome of these patients. Study design: We retrospectively analyzed all cases of UT torsion operated in nine French hospitals between 1997 and 2017. We divided patients in two groups: patients referred less than 6 h after the onset of symptoms (group A) or more than 6 h (group B). Main results: We collected 60 cases (17 in group A and 43 in group B). Median age was 2.2 years [IQR = 0.7–7.8] (2.3 y in group A and 2 y in group B, p = 0.76). Eleven patients (10 in group B) had neurological disorders (p = 0.15). The main reason for absence of UT treatment was the absence of surgical consultation in a normal delay (n = 44, 73%). Symptoms were pain (n = 58, 97%), inguinal mass (n = 55, 92%) and vomiting (n = 16, 27%). An inguinal mass with no palpable testis in the ipsilateral hemiscrotum was seen in 55 patients (92%). An ultrasound scan performed in 27 patients led to the diagnosis in 16 patients (59%). At surgery, an orchiectomy was performed in 4 patients (23%) of group A and 24 patients (56%) of group B (p = 0.04). After a median follow-up of 11 months [IQR = 4–23], 11 patients of group A (65%) and 7 patients of group B (16%) had a clinically normal testis (p = 0.03). The salvage rate among patients with conservative treatment was 85% for group A and 37% for group B (p = 0.01). Discussion: Our study reveals that although UT torsion is an emergency, 72% of patients are referred more than 6 h after the onset of symptoms. We mostly found classic clinical presentation of UT torsion: a painful inguinal mass with an empty ipsilateral scrotum. Ultrasound was performed in half cases, and even if the result was not significant, it still seemed to be associated with a higher rate of orchiectomy especially in group B because of the delay in care. However, when ultrasound was realized early, it led to diagnosis in all cases. This dilemma poses the problem of the role of imaging in diagnostic management. Conclusions: Early clinical diagnosis in front of a painful inguinal mass with an empty scrotum is essential to improve the salvage rate of testis in UT torsion. Early management of UT should have avoided 68% of testis loss. Summary Table Operative findings and follow-up Summary Table Group A (n = 17) Group B (n = 43 a ) TOTAL (n = 60) p-value Testis appearance, n (%) Ischemic 10 (59) 10 (23) 20 (33) 0.01 Necrotic 5 (30) 26 (61) 31 (52) 0.04 Vascularized 2 (11) 7 (16) 9 (15) 0.99 Orchiectomy, n (%) 4 (23) 24 (56) 28 (47) 0.04 Orchidopexy of the contralateral testis, n (%) 2 (12) 15 (35) 17 (28) 0.11 Testis atrophy at last follow-up, n (%) 2 (12) 8 (18) 10 (31) 0.05 Normal clinical testis at last follow-up, n (%) 11 (65) 7 (16) 18 (30) 0.03 a Four patients were lost to follow-up.